Religion, Politician Identity and Development Outcomes: Evidence from India - Sonia R. Bhalotra; Irma Clots-Figueras; Guilhem Cassan; Guilhem Lakshmi Iyer Cassan (Institute for the Study of Labor (IZA), 2013)
This paper investigates whether the religious identity of state legislators in India influences development outcomes, both for citizens of their religious group and for the population as a whole. To control for politician identity to be correlated with constituency level voter preferences or characteristics that make religion salient, we use quasi-random variation in legislator identity generated by close elections between Muslim and non-Muslim candidates. We find that increasing the political representation of Muslims improves health and education outcomes in the district from which the legislator is elected. We find no evidence of religious favoritism: Muslim children do not benefit more from Muslim political representation than children from other religious groups.
Keywords: I15; J13; H41; P16; 330; religion; politician identity; infant mortality; primary education; India; Muslim; Religionsgemeinschaft; Islam; Patronage; Regionale Entwicklung; Indien